Design of civil defense protective structures in residential multi-story buildings for individual use - Filonenko, Olena; Nikolaienko, Dmytro (Academic journal Industrial Machine Building Civil Engineering, 2025)
The military actions in Ukraine, which daily create a threat to the civilian population, necessitate the development of new technical solutions for new construction and the reconstruction of existing buildings and structures. A large number of civilian casualties are residents of multi-story residential buildings. A typical protective shelter is considered to be a basement or cellar floor, the structural features of which are designed for utilities, pipelines, and technical equipment. They lack an emergency exit and proper ventilation, and do not provide for long-term stay with specific conditions in full compliance with the current regulatory requirements for the protection of the civilian population. As a result of the analysis of architectural and planning solutions, there is a need to improve premises where it is possible to integrate individual protective shelters, which are intended to provide proper protection in case of an emergency. The work examines the fundamental principles of approaches to designing individual protective shelters within the housing stock. The proposed recommendations can be used in designing new residential buildings, reconstructing existing buildings, and forming a system of individual protective shelters aimed at increasing the level of public safety in modern conditions.
Keywords: civil defense structures; protective premises; design of civil defense facilities; housing stock